2010
DOI: 10.1177/0333102410368445
|View full text |Cite
|
Sign up to set email alerts
|

Case series of sixteen patients with nummular headache

Abstract: Our series results support previous findings. In our population, no specific therapy was identified to be effective in more than one patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 13 publications
1
45
1
1
Order By: Relevance
“…It is interesting that the frequency of migraine in our series is lower than in the previously reported studies of autoimmune disorder patients [15][16][17][18]22] and a report of 16 NH patients [27]. If autoimmune-mediated NH and migraine or other headache syndromes counteract with each other warrants further investigation.…”
Section: Discussioncontrasting
confidence: 60%
“…It is interesting that the frequency of migraine in our series is lower than in the previously reported studies of autoimmune disorder patients [15][16][17][18]22] and a report of 16 NH patients [27]. If autoimmune-mediated NH and migraine or other headache syndromes counteract with each other warrants further investigation.…”
Section: Discussioncontrasting
confidence: 60%
“…Some patients have shown trophic changes within the painful area, including thinness of the skin, and one patient had hair heterochromia at the pain site . There are a few cases reported with the painful area larger than 6 cm of diameter – up to 10 cm . Some studies have shown evidence of increased sensitivity – a lower pain threshold with pressure algometry – restricted to the symptomatic area, with no pericranial tenderness in the remainder of the scalp, and with no signs of a generalized pain state …”
Section: Resultsmentioning
confidence: 99%
“…Fernández‐de‐las‐Peñas and colleagues have shown that NH is not associated with either depression or anxiety. A few patients have reported mild head trauma previous to the onset of NH . Many patients have also a past or present diagnosis of migraine, but the pain from a migraine headache can be easily distinguished from the NH pain .…”
Section: Resultsmentioning
confidence: 99%
“…Despite its recent first description, the phenotype of NH is now well established because of the reports of multiple cases 1,3,5,7‐17 . Since the original diagnostic criteria were proposed in the ICHD‐II appendix, 2 new case descriptions have expanded the clinical spectrum of NH.…”
Section: Discussionmentioning
confidence: 99%